Prinsip-Prinsip Komunikasi Dakwah Berbasis Media Online: (Studi Retorika KH. Buya Syakur Yasin Pada Channel Akun Youtube KH Buya Syakur Yasin MA) - Siti Hudayana Husri (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
This research examines the principles of online media-based da'wah communication through a rhetorical study conducted by KH. Buya Syakur Yasin on the YouTube channel KH Buya Syakur Yasin MA. The aim of this research is to identify the da'wah communication messages and rhetorical styles employed by Buya Syakur Yasin on the YouTube channel KH Buya Syakur Yasin MA. The research methodology utilized a qualitative approach with a qualitative descriptive approach. Data was collected through observation and documentation and then analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that (1) there are three forms of da'wah communication messages delivered by Buya Syakur: religious messages, moral and ethical messages, and an understanding of Islam. (2) The rhetorical style employed includes simplicity, the use of real-life examples, empathy, and the maintenance of consistency and authenticity in da'wah efforts. This research is expected to make a significant contribution to the development of da'wah strategies.